2009
DOI: 10.1088/1752-7155/3/4/047003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atropine sulfate on gastric emptying and gastrocecal transit time evaluated by using the [1- 13 C]acetic acid and lactose-[ 13 C]ureide breath test in conscious rats

Abstract: Breath tests have been used to investigate many physiological functions. Recently, we have developed a breath test system by using a non-invasive technique in conscious rats. In this study, we investigated the effect of atropine sulfate on the gastric emptying and gastrocecal transit time using [1-(13)C]acetic acid and lactose-[(13)C]ureide, respectively. Gastric emptying was significantly delayed by atropine sulfate in a dose-dependent manner (0.03-0.3 mg kg(-1)), but the effects of 0.1 and 0.3 mg kg(-1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…This may promote reabsorption of materials in the intestine due to decrease propulsion of material in the intestinal tract, and the extract might have exerted its antidiarrhoeal action by antisecretory mechanism. This result similar to obtained by Izzo et al (1999) and Uchida et al (2009).…”
Section: Anti-enteropooling Testsupporting
confidence: 92%
See 1 more Smart Citation
“…This may promote reabsorption of materials in the intestine due to decrease propulsion of material in the intestinal tract, and the extract might have exerted its antidiarrhoeal action by antisecretory mechanism. This result similar to obtained by Izzo et al (1999) and Uchida et al (2009).…”
Section: Anti-enteropooling Testsupporting
confidence: 92%
“…The plant extract inhibited normal gastric emptying; this effect may be linked to the reduction in gastrointestinal propulsion observed in the rats. (Izzo et al, 1999;Camilleri, 2004;Uchida et al, 2009) showed decrease in intestinal transit time by morphine and atropine is linked to delays in gastric emptying. This suggests that the plant may have morphine-like action in exerting its antidiarrhoeal activity.…”
Section: Advances In Animal and Veterinary Sciences March 2016 | Volumentioning
confidence: 99%
“…In this study, we used a liquid test meal containing [1-13 C] acetic acid as the labeled compound, because a solid test meal is hard for the rats to ingest within a short limited time, although Hoshino et al (2008) reported breath testing using a solid test meal in mice. Until now, we have usually used 8 mg/kg of [1-13 C] acetic acid as the dose for the evaluation of gastric emptying (Uchida et al, 2005;Uchida et al, 2007;Uchida et al, 2011;Uchida et al, 2009b). However, in the present study we used 4 mg/kg of [1-13 C] acetic acid, because a larger dose of [1-13 C] acetic acid would affect the level of the expired 13 CO 2 derived from the simultaneously administered lactose-[ 13 C] ureide.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, we have also established a non-invasive and feasible method for the evaluation of rat gastrocecal transit time by using lactose-[ 13 C] ureide (Uchida et al, 2009a) and the effect of atropine sulfate which significantly delayed the gatsrocecal transit time (Uchida et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…The neurotransmitters nitric oxide (NO) and vasoactive intestinal peptide (VIP), found in the myenteric plexus, exert critical inhibitory roles on gut smooth muscle cells (10). High-intensity exercise raises blood levels of NO and VIP (11), but also promotes the release of corticosterone (12). Additionally, atropine has been shown to delay GE (13).…”
Section: Introductionmentioning
confidence: 99%